Preclinical investigations of the efficacy of the glutaminase inhibitor CB-839 alone and in combinations in chronic lymphocytic leukemia - Timofeeva, Natalia; Ayres, Mary L.; Baran, Natalia; Santiago-O’Farrill, Janice M.; Bildik, Gamze; Lu, Zhen; Konopleva, Marina; Gandhi, Varsha (Frontiers in Oncology, 2023)
Chronic lymphocytic leukemia (CLL) cells are metabolically flexible and adapt to modern anticancer treatments. Bruton tyrosine kinase (BTK) and B-cell lymphoma-2 (BCL-2) inhibitors have been widely used to treat CLL, but CLL cells become resistant to these treatments over time. CB-839 is a small-molecule glutaminase-1 (GLS-1) inhibitor that impairs glutamine use, disrupts downstream energy metabolism, and impedes the elimination of reactive oxygen species. To investigate the in vitro effects of CB-839 on CLL cells, we tested CB-839 alone and in combination with ibrutinib, venetoclax, or AZD-5991 on the HG-3 and MEC-1 CLL cell lines and on primary CLL lymphocytes. We found that CB-839 caused dose-dependent decreases in GLS-1 activity and glutathione synthesis. CB-839–treated cells also showed increased mitochondrial superoxide metabolism and impaired energy metabolism, which were reflected in decreases in the oxygen consumption rate and depletion of the adenosine triphosphate pool and led to the inhibition of cell proliferation. In the cell lines, CB-839 combined with venetoclax or AZD-5991, but not with ibrutinib, demonstrated synergism with an increased apoptosis rate and cell proliferation inhibition. In the primary lymphocytes, no significant effects of CB-839 alone or in combination with venetoclax, ibrutinib, or AZD-5991 were observed. Our findings suggest that CB-839 has limited efficacy in CLL treatment and shows limited synergy in combination with widely used CLL drugs.